Decellularized and Engineered Tendons as Biological Substitutes: A Critical Review - Arianna B. Lovati; Marta Bottagisio; Matteo Moretti (Hindawi Limited, 2016)
Tendon ruptures are a great burden in clinics. Finding a proper graft material as a substitute for tendon repair is one of the main challenges in orthopaedics, for which the requirement of a biological scaffold would be different for each clinical application. Among biological scaffolds, the use of decellularized tendon-derived matrix increasingly represents an interesting approach to treat tendon ruptures. We analyzed in vitro and in vivo studies focused on the development of efficient protocols for the decellularization and for the cell reseeding of the tendon matrix to obtain medical devices for tendon substitution. Our review considered also the proper tendon source and preclinical animal models with the aim of entering into clinical trials. The results highlight a wide panorama in terms of allogenic or xenogeneic tendon sources, specimen dimensions, physical or chemical decellularization techniques, and the cell type variety for reseeding from terminally differentiated to undifferentiated mesenchymal stem cells and their static or dynamic culture employed to generate implantable constructs tested in different animal models. We try to identify the most efficient approach to achieve an optimal biological scaffold for biomechanics and intrinsic properties, resembling the native tendon and being applicable in clinics in the near future, with particular attention to the Achilles tendon substitution.